Forgiveness and Personality Type among Men and Women Suffering from Cardiovascular Diseases (Delta Medical College Journal, 2014)
Background: Role of personality and some components of behaviors, traits and emotions as effective factors on coronary heart diseases (CHD) were presented nearly 50 years ago with the concept of type A behavior, a compound of hostility, impatience, competitiveness and dominance. Later studies showed crucial role of other traits and behaviors like anger, introversion, depression and forgiveness. Objective: The aim of this study was to compare personality type and forgiveness in the patients suffering from cardiovascular diseases based on gender. Materials and method: The cross sectional study was designed and sample was collected from men and women referred to cardiologists (within the age range of 23-75 years old) from the patients of Shahid Rajaee Heart Hospital of Tehran, Iran from December 2010 to March 2011. Total 87 subjects were selected using random method. The study subjects were given two questionnaires: personality type A (with two factors: TA1, pathologic behaviors of type A personality and TA2, non pathologic behaviors of type A personality) and Interpersonal Forgiveness Inventory (IFI), with three subscales namely reestablishment of relationship, control of revenge and realistic perception. Data were analyzed using SPSS software. Results: Mean(±SD) age of men was 50.5±11.6 years (n=33) and 55.7±14.4 years in women (n=54). Mean duration of suffering from cardiovascular diseases in men was 7.8 years and in women was 9.10 years. The study found high mean scores of type A pathologic but not non pathologic type A among women compared to men (p